OPTIMASI SUBSTITUSI PASIR PANTAI SEBAGAI PENGGANTI PASIR SUNGAI PADA SISTEM PEMBUATAN PAVING BLOCK - , MUKHIBIN ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Indonesia is an archipelago that is automatically there are many beaches in each of the island, contain sand beach that almost has a similarity. However, this material has known yet the potential and properties when use as a substitute for river sand, especially sand beach that located in the Village the Setrojenar Buluspesantren Kebumen district of Central Java and its surroundings. Use of beach sand as a raw material alternative to river sand should be economically much cheaper, can and no immersion treated using, can also reduce the dependence on only one raw material, while also reducing the impact of degradation in the surrounding watershed (DAS). Manufacture of paving blocks made of cement, water and beach sand 2, and 5 days immersion, and no immersion treated using then paving blocks that are made from cement porlland, beach sand and water them are soaked for 7, 14, 21, and 28 days. Further, more these paving block were tested to measure the chemical, physical, and mechanical properties to determine the characteristics of the paving block. The results ot this research, longer immersion of beaches sand will increase the compressive strength. Compressive strength of paving blocks using the treated beach sand for 7 days aged soaking has the compressive strength = 251, 09 kg/cm2, while using the untreated beach sand/ no immersion has the average compressive strength of 254,14 kg/cm2 for 28 days aged. The conclusion that this using of the treated/untreated beach sand as a substitution material for river sand in production paving block full fill the requirement of SK-SNI-03-0691-1996 a class B. This requirement is, the minimum compressive strength should be 246,12 kg/cm2